The effect of light source distance on diametral tensile strength of nano particle composite - Febrida, Renny; Herda, Ellyza; Soufyan, Andi (Padjadjaran Journal of Dentistry, 2008)
The use of nano particle composite in posterior region is somehow difficult due to the limited space to place the light source as close as possible to the restorative material. The distance between the light source and restorative material surface leads to decreased light intensity that causing inadequate polymerization. The inadequate polymerization affects the composite diametral tensile strength. Two types of nano particle composite, i.e. FiltekTM Z-350 and Ceram-XTM were tested for their diametral tensile strength, which is affected by the distance of the light source from the composite material surface. Some cylindrical specimens were exposed to light with various distances from the light source, i.e. 0, 1, 2, 3, 4, and 5 mm from the specimen surface. From the six distance variations tested the diametral tensile strength of Filtek Z-350 is 64.09-58.20 MPa with the significant result in 2, 3, 4 and 5 mm distances; and the diametral strenght of Ceram-X is 47.52-42.20 MPa with the significant result in 2, 3, 4 and 5 mm distances. The results of this study show that the increased distance of the light source from the nano particle composite restorative material leads to decreased diametral strength of the two nano particle composites tested.